A novel lanthanum-modified copper tailings adsorbent for phosphate removal from water. (October 2021) - Jin, Haiyang; Lin, Li; Meng, Xiaoyang; Wang, Linling; Huang, Zhuo; Liu, Min; Dong, Lei; Hu, Yuan; Crittenden, John C.
Abstract: La(OH)3 -modified copper tailings were prepared, characterized, and investigated for phosphate removal from water in this study. Scanning electron microscopy (SEM) analysis showed that La(OH)3 modification made a large amount of spherical solid agglomerates appeared on the surface of the copper tailings and created many pores. Laser particle size analysis indicated that the modified copper tailings had much a smaller particle size and larger specific surface area. Fourier Transform Infrared Spectroscopy (FTIR) and X-ray fluorescence (XRF) analysis illustrated that lanthanun was successfully loaded on the copper tailings with a mass percentage of 25.31%. The adsorption kinetics and isothermal adsorption experiment results indicated that the La(OH)3 -modified copper tailings had a much better phosphate adsorption capacity than the original copper tailings. The adsorption kinetics process of the La(OH)3 -modified copper tailings followed the pseudo-second-order kinetic model, and the isothermal adsorption data were well fitted by the Langmuir isotherm model. The maximum phosphorus adsorption capacity of the copper tailings after alkali treatment and La(OH)3 modification increased from 737.04 mg/kg to 7078.43 mg/kg, which was close to that of Phoslock. Leaching toxicity testing demonstrated that the use of La(OH)3 -modified copper tailings for phosphorus removal in water treatment would not cause secondary pollution. Adsorption mechanism analysis revealed that both electrostatic attraction and ligand exchange were involved in phosphate adsorption onto La(OH)3 -modified copper tailings. The phosphate adsorption of La(OH)3 -modified copper tailings was pH-dependent, and a high-pH environment resulted in a decline in adsorption capacity. The increased concentration of OH − in high-pH solution was unfavorable for ligand exchange between phosphate species and hydroxyl groups from La(OH)2 species. In addition, competitive adsorption between HPO4 2− and the increased amounts of OH − weakened electrostatic attraction. The results suggested that La(OH)3 -modified copper tailings are promising adsorbents for highly efficient phosphate removal and provide a new method to realize the resource utilization of copper tailings. Graphical abstract: Image 1 Highlights: La(OH)3 -modified copper tailings were successfully prepared. La(OH)3 -modified copper tailings had much a smaller particle size and larger specific surface area than the original copper tailings. La(OH)3 -modified copper tailings showed high phosphate adsorption capacity and the use for phosphorus removal would not cause secondary pollution. Both electrostatic attraction and ligand exchange were involved in phosphate adsorption onto La(OH)3 -modified copper tailings. La(OH)3 -modified copper tailings are promising adsorbents for phosphate removal and could thus realize the resource utilization of copper tailings.